Nanoparticles as a Solution for Eliminating the Risk of Mycotoxins - Horky, Pavel; Skalickova, Sylvie; Baholet, Daria; Skladanka, Jiri (Nanomaterials (Basel, Switzerland), 2018)
Mycotoxins are toxic secondary metabolites produced by certain filamentous fungi. The occurrence of mycotoxins in food and feed causes negative health impacts on both humans and animals. Clay binders, yeast cell walls, or antioxidant additives are the most widely used products for mycotoxin elimination to reduce their impact. Although conventional methods are constantly improving, current research trends are looking for innovative solutions. Nanotechnology approaches seem to be a promising, effective, and low-cost way to minimize the health effects of mycotoxins. This review aims to shed light on the critical knowledge gap in mycotoxin elimination by nanotechnology. There are three main strategies: mold inhibition, mycotoxin adsorption, and reducing the toxic effect via nanoparticles. One of the most promising methods is the use of carbon-based nanomaterials. Graphene has been shown to have a huge surface and high binding capacity for mycotoxins. Attention has also been drawn to polymeric nanoparticles; they could substitute adsorbents or enclose any substance, which would improve the health status of the organism. In light of these findings, this review gives new insights into possible future research that might overcome challenges associated with nanotechnology utilization for mycotoxin elimination from agricultural products.
Keywords: nanotechnology; agriculture; toxicity; nanoparticles; mycotoxin